Assessment of farmers' knowledge, attitudes and control practices (KAP) to mitigate acaricide resistance and tick-borne diseases - Sunita Jamra; Mukesh Shakya; Anant K. Jayraw; Vivek Agrawal; Mamta Singh; Anil Kumar Sharma; Gajendra N. Bhangale; Gaya P. Jatav; Nirmala Jamra; Ala Tabor (Parasitology)
A knowledge, attitudes and control practices (KAP)-based study on ticks and tick-borne diseases (TTBD) and resistance development in ticks was conducted in Dhar district of Madhya Pradesh covering 200 livestock owners using a questionnaire. Based on our scoring criteria, results indicated only 25% (19.16–31.60) respondents possessing basic knowledge of TTBDs while 75% (68.40–80.84) respondents were not aware of TBDs. Due to lack of proper awareness of TTBDs, about 1.28 times more respondents (OR 95% CI 0.42–3.86) were having heavy tick infestations in their animals. However, about 36.5% (29.82–43.58) respondents showed a favourable attitude towards the adoption of different tick control practices; consequently, their animals showed low-level infestation. Amongst various feeding systems for animals, a mixed type of feeding system was mostly adopted by 57.5% respondents followed by manger system (37.5%) while grazing was the least adopted method (5%). Results indicated that the grazing animals were 6 times (OR 95% CI 2.93–12.28) more susceptible to ticks and possessed heavy tick infestation. Resistance status of collected tick isolates of Rhipicephalus microplus and Hyalomma anatolicum was assessed and revealed that both tick species were found resistant to deltamethrin. The goals of this study were to assess some of the underlying causes of ticks and TBD in livestock in Dhar district of Madhya Pradesh state using the KAP survey and resistance characterization of ticks.